BECOMING A GREAT PARENT: PARENT-CHILD COMMUNICATION IN ANTICIPATION OF GADGETS ADDICTION - Adeni, Susri; Machyudin Agung Harahap (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
The impact of gadget use on children poses significant challenges, necessitating effective parental intervention to prevent gadget addiction. This qualitative descriptive study was conducted within the Taklim Keluarga Sakinah (TKS) group in Bengkulu City. The research aimed to explore how parents and children communicate to anticipate and manage gadget addiction within the family. Data were collected from five informants who are members of TKS using online questionnaires and interviews. The findings revealed that parents play a pivotal role in fostering effective communication with their children, employing strategies such as setting clear rules for gadget use, engaging in gentle and empathetic dialogue, and consistently implementing agreed-upon boundaries. While children occasionally exhibited emotional reactions such as anger or frustration when restricted, these were effectively mitigated through constructive parental communication and engaging children in alternative activities. The study underscores the importance of parental mediation and supports integrating digital literacy education in schools to reinforce responsible gadget use. This research provides valuable insights for families and educators in promoting healthy digital habits and mitigating the risks associated with excessive gadget use.